Common state mechanisms regulating tribal tobacco taxation and sales, the USA, 2015. (27th June 2016) - DeLong, Hillary; Chriqui, Jamie; Leider, Julien; Chaloupka, Frank J
Abstract : Background: Native American tribes, as sovereign nations, are exempt from state tobacco excise taxation, and self-govern on-reservation activity in the USA. Under Federal law, state excise taxes are owed by non-members purchasing tobacco on tribal land, but states are limited in how they enforce or collect these taxes. This study highlights the various policy approaches that states have taken to regulate tobacco sales on tribal lands given jurisdictional challenges. Methods: State laws (statutes, regulations and case law), Attorney General opinions, and revenue notices and rulings effective as of 1 January 2015 for all 50 states and the District of Columbia were compiled using Boolean searches in Lexis-Nexis and Westlaw. Laws were limited to those addressing taxation compacts or tobacco sales involving tribal entities. Master Settlement Agreement laws and non-codified tribal codes/compacts were excluded. Results: Twenty of the 34 states with tribal lands address tribal tobacco sales. Fourteen states address intergovernmental compacts: 11 are tobacco specific, and suggest or require specific provisions. Fifteen states address tribal tax stamps: 2 explicitly prohibit stamping tribally sold products, 9 stamp all products, and 4 stamp some. Prepayment of excise tax is required in 12 states: 6 on all products, 4 on products in excess of quota, and 2 on products sold by non-tribal retailers. 6 states use quotas to limit tax-free tobacco available to tribes. Conclusions: Many states with a tribal presence have no formal strategies for non-members purchasing tobacco on tribal lands. Formalising policies and harmonising tax rates may assist states in collecting tax revenue from non-tribal consumers.